Kerathocyst Odontogenic Tumor: Importance of Selection the Best Treatment Modality and A Periodical Follow-up to Prevent from Recurrence: A Case Report and Literature Review - Jafaripozve, Nasim (Medknow Publications & Media Pvt Ltd, 2013)
The keratocystic odontogenic tumor (KCOT) is a relatively common oral and maxillofacial lesion with specific characteristics such us rapid growth, extension into the surrounding tissues and high rates of recurrence. Various treatment modalities have been reported. Due to the very thin and friable lining characteristic of the tumor, enucleation can be difficult undertaken and for this reason it is associated with the highest recurrence rates. A 22-year-old male referred to our clinic due to a slight expansion in the right mandible from 2 years ago. He has a history of occurrence of KCOT in this region that was treated surgically by enucleation and curettage 5 years ago. Cone beam computed tomography showed a multilocular radiolucent lesion that extended from the angle of the mandible to the symphysis. Incisional biopsy showed a KCOT recurrence that surgically treated with resection of the right mandible by continuity preservation. Selection of the best treatment modality and also a periodical lifelong follow-up is very important to reduce the rate of recurrence and morbidity of the patient.